The association between idiopathic thrombocytopenic purpura and cardiovascular disease: a retrospective cohort study. (5th February 2018) - Chandan, J. S.; Thomas, T.; Lee, S.; Marshall, T.; Willis, B.; Nirantharakumar, K.; Gill, P.
Abstract : Essentials We estimated the cardiovascular risk of patients with idiopathic thrombocytopenic purpura (ITP). The risk of cardiovascular disease was 38% higher in ITP patients compared with controls. Among the ITP patients, splenectomy was associated with higher cardiovascular disease. Clinicians should consider cardiovascular risk when managing ITP patients. Summary: Background: Idiopathic thrombocytopenic purpura (ITP) is classically characterized by a transient or persistent decrease of platelet count. Mortality is higher in the ITP population than the general population, with a possible association with increased cardiovascular disease (CVD). Objectives: The objective was to assess the strength of the association between ITP and CVD, with a secondary aim to assess the impact of splenectomy on CVD. Methods: A population‐based retrospective, open cohort study using clinical codes was performed using data from 6591 patients with ITP and 24 275 randomly matched controls (up to 1:4 ratio matched by age, sex, body mass index and smoking status). The main outcome was the risk of CVD, which included ischemic heart disease, stroke, trans‐ischemic attack and heart failure. Adjusted incidence rate ratios were calculated using Poisson regression. Results: During a median 6‐year observation period there was a CVD diagnosis recorded in 392 (5.9%) ITP patients and 1114 (4.5%) control patients. There was an increased risk of developing CVD in the ITP cohort (incidence rate ratio [IRR], 1.38; 95% confidence interval [CI], 1.23–1.55), which remained robust even after a sensitivity analysis only including incident cases of ITP. Findings suggested that patients who had undergone splenectomy were at even further increased risk of developing CVD when compared with the ITP population who had not undergone splenectomy (adjusted IRR, 1.69; 95% CI, 1.22–2.34). Conclusion: There is an increased risk of developing CVD in patients with ITP and even further increased risk for those patients with ITP who underwent splenectomy.